Imaging Cultural Heritage at Different Scales: Part II, the Meso-Scale (Sites) - Luca Piroddi; Nasser Abu Zeid; Sergio Vincenzo Calcina; Patrizia Capizzi; Luigi Capozzoli; Ilaria Catapano; Marilena Cozzolino; Sebastiano D’Amico; Rosa Lasaponara; Deodato Tapete (Remote Sensing)
Non-invasive sensing techniques have become a cornerstone in the study and preservation of Cultural Heritage. These techniques offer a means to investigate the internal structure and surface properties of precious and delicate objects without causing damage. This article is the second of three review articles exploring contact and non-contact imaging methods applied to Cultural Heritage at various scales encompassing micro- (i.e., manufacts), meso- (sites), and macro-scales (landscapes). The unifying factor of these techniques is their ability to infer variations in geometrical and physical properties across inspected surfaces or volumes. This allows researchers to discover new historical sites, map their spatial extent, and characterize their material features at different scales, from landscapes to artifacts. This second part focuses on the meso-scale, encompassing the inspection, documentation, study, and characterization of historical and archeological sites, monuments, and submerged sites, using both contact and remote sensing techniques.